Keabsahan Akad Nikah melalui Video Call menurut Hukum Islam - Mochamad Adrian Pranata; Neneng Nurhasanah; Muhammad Yunus (Bandung Conference Series: Islamic Family Law, 2021)
Abstract. Islamic law emphasizes that "marriage is a form of muqayyah worship. Its validity lies in its terms and harmony. Therefore it requires / requires the presence of contracted parties, meanwhile with the development of technology, the marriage contract through the media of video calls is not considered valid if the terms and conditions are not met. The pillars or essential elements are consent and qabul. The problem points formulated in this study are How Marriage via video call media according to Islamic Law, how is the validity of the Marriage Contract through video call according to Islamic Law. The research method used is the normative juridical method. Which is the object of Marriage Contract Research through video call media according to Islamic Law. The purpose of this research: To know marriage through video call media according to Islamic law, to know the validity of the marriage contract through video call media according to Islamic law. The results of the study concluded that: Marriage via video call is a consent statement uttered by the female guardian which is then answered by the male, based on technological advances through the internet media. The marriage contract through legal video call media fulfills the requirements and harmonious marriage, does not contradict Islamic law, such as a prospective husband and a female marriage guardian, two witnesses and a consent of Kabul. This is confirmed by the provisions of Article 27 to 29 Compilation of Islamic Law, among others, not intermittent, carried out directly by the guardian of marriage concerned and pronounced directly by the groom through a video call, then fulfilled, among others, harmonious, legal requirements, conditions of marriage. Abstrak. Hukum Islam menegaskan bahwa “perkawinan dinyatakan bentuk ibadah muqayyah keabsahannya terletak pada syarat dan rukunnya. Oleh karena itu mengharuskan/mensyaratkan hadirnya pihak-pihak yang berakad, sementara itu dengan perkembangan teknologi maka akad nikah melalui media video call, tidak dianggap sah jika syarat dan rukunnya ada yang tidak terpenuhi. Rukun-rukun atau unsur-unsur esensialnya adalah ijab dan qabul. Poin masalah yang dirumuskan dalam penelitian ini adalah bagaimana pernikahan melalui media video call menurut Hukum Islam, Bagaimana Keabsahan Akad Nikah melalui media video call menurut Hukum Islam. Metode penelitian yang digunakan adalah metode yuridis normatif. yang menjadi Objek Penelitian Akad Nikah melalui media video call menurut Hukum Islam. Tujuan penelitian ini: Untuk mengetahui Pernikahan melalui media Video call menurut Hukum Islam, Untuk mengetahui Keabsahan Akad nikah melalui media Video call menurut Hukum Islam. Hasil penelitian menyimpulkan bahwa: Pernikahan melalui media video call merupakan pernyataan ijab yang diucapkan oleh wali pihak perempuan yang kemudian dijawab oleh pihak laki-laki, berdasarkan kemajuan teknologi melalui media internet. Akad nikah melalui media video call sah memenuhi syarat dan rukun perkawinan, tidak bertentangan dengan hukum islam, seperti adanya calon suami dan, wali nikah pihak perempuan, dua orang saksi dan ijab kabul. Hal ini dikuatkan dengan ketentuan pasal 27 sampai dengan 29 Kompilasi Hukum Islam antara lain tidak berselang waktu, dilakukan langsung oleh wali nikah yang bersangkutan dan diucapkan langsung oleh mempelai laki-laki melalui video call. Kemudian, terpenuhi antara lain rukun, syarat sah, syarat-syarat perkawinan.